Probabilistic Analysis of Different Redundant Complex System with Reper for the Unites - Entesar AL-Esayeh (AlQalam Journal of Medical and Applied Sciences, 2024)
This paper presents the reliability and MTTF analysis of a two-state complex with repairable system, consisting of two sub-systems A and two sub-systems B arranged in series, incorporating the concept of hardware failures. Laplace transforms of the various state probabilities have been derived and then reliability of the complex system, at any time t, has been computed by inversion process. MTTF has also been evaluated; availability and steady-state availability for system are derived. The failure times of operating units and repair time of failed units are exponential distributed. Certain important results have been evaluated as special cases. Also, few graphical illustrations are also given at the end to high-light the important results. نرغب من هذه الدراسة طريقة للوصول الى اعلى درجات الصلاحية لنظام قابل للإصلاح مكون من وحدتين (أ، ب) متماثلتين موصلتين على التوالي .علما ان الوحدة "أ" مكونة من وحتين جزيتين موصلتين على التوازي كل منهما تتعرض لنوعين من الخطأ (خطأ بشري ,خطأ الالة) وكذلك الوحدة "ب" تتكون من وحدتين موصلتين على التوازي كل منهما تتعرض لنوعين من الخطأ (خطأ بشري ,خطأ الالة) ومن بعد اعتماد الرسم البياني لهذا النظام نحاول استنتاج المعادلات التفاضلية الانتقالية وثم حل هذه المعادلة باستخدام المصفوفات ثم الحصول على الدالة الاحتمالية واحتمال تعرض النظام لخطأ الالة علما بان النظام يتوقف عن العمل عند فشل الوحدة "أ" كليا او فشل الوحدة "ب" كليا . وباعتبار معدل الفشل والتصليح للوحدتين متغيرات عشوائية يتبعان التوزيع الاسي الثابت ونحاول الوصول الي حساب العلاقة بين معدل الفشل والنفاعية خلال الزمن وتمثيل ذلك بيانيا. كذلك حساب العلاقة بين احتمال فشل النظام الناتج من خطأ الالة ومعدل فشل الوحدة "أ" نتيجة خطأ الالة. كذلك حساب العلاقة بين احتمال فشل النظام الناتج من الخطأ البشري ومعدل فشل الوحدة "أ" نتيجة خطأ بشري. (يتم اشتقاق تحويلات لا بلاس في حل المعادلات الخاصة بالنظام)